2012
DOI: 10.1097/cad.0b013e3283512726
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in improved efficacy of doxorubicin chemotherapy in Cbr1+/− mice

Abstract: The anthracycline chemotherapeutic agent doxorubicin is converted by the enzyme carbonyl reductase 1 (CBR1) into its cardiotoxic metabolite doxorubicinol. Cbr1+/- mice have been shown to be protected from doxorubicin-induced cardiotoxicity, and the inhibition of CBR1 activity may be a useful means of ameliorating the side effects of doxorubicin in patients undergoing chemotherapy. Because reduced conversion to doxorubicinol increases circulating levels of the more effective parent drug doxorubicin, it was hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Sex hormones may also participate in CBR1 transcriptional regulation, as a marked difference in Cbr1 expression between male and female mice has been reported (Freeland et al, 2012). This finding points to the possibility that the anticancer as well as adverse effects of anthracyclines may differ between genders.…”
Section: The Transcriptional Regulation Of Cbr1mentioning
confidence: 86%
“…Sex hormones may also participate in CBR1 transcriptional regulation, as a marked difference in Cbr1 expression between male and female mice has been reported (Freeland et al, 2012). This finding points to the possibility that the anticancer as well as adverse effects of anthracyclines may differ between genders.…”
Section: The Transcriptional Regulation Of Cbr1mentioning
confidence: 86%
“…Several investigators attributed this sexual dimorphism to the cardioprotection conferred by estrogen in female experimental animals [11, 13, 45]. Intriguingly, another study showed that the expression of carbonyl reductase, a major DOX-metabolizing enzyme, is higher in the kidney and liver of female than in male mice [46]. The authors suggested that higher expression of carbonyl reductase may make female mice more sensitive to DOX-induced toxicity; however, DOX-induced cardiotoxicity was not actually assessed in their study [46].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, another study showed that the expression of carbonyl reductase, a major DOX-metabolizing enzyme, is higher in the kidney and liver of female than in male mice [46]. The authors suggested that higher expression of carbonyl reductase may make female mice more sensitive to DOX-induced toxicity; however, DOX-induced cardiotoxicity was not actually assessed in their study [46]. Therefore, the underlying mechanisms of sexual dimorphism in DOX-induced toxicity are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the highest DOX concentration was found in the urine of DOX-IN-treated animals after the last injection, which implies the higher organ toxicity of the conventional DOX formulation compared to the nanoformulation. As DOX is mostly metabolized by the liver, the higher excretion of unchanged DOX means a lower capacity of the liver to metabolize it [37,38]. This was also evident in the results obtained for DOXol and DOXon concentrations, which decreased with the number of applications in animals treated with DOX-IN.…”
Section: Discussionmentioning
confidence: 65%